Beyond single-stream with the Schrödinger method. Issue Volume 11:Issue S308(2015) (12th October 2016) - Uhlemann, Cora; Kopp, Michael
Abstract: We investigate large scale structure formation of collisionless dark matter in the phase space description based on the Vlasov-Poisson equation. We present the Schrödinger method, originally proposed by \cite{WK93} as numerical technique based on the Schrödinger Poisson equation, as an analytical tool which is superior to the common standard pressureless fluid model. Whereas the dust model fails and develops singularities at shell crossing the Schrödinger method encompasses multi-streaming and even virialization.